Preliminary experience of a modified Maquet technique for repair of cranial cruciate ligament rupture in dogs - Etchepareborde, S.; Brunel, L.; Bollen, G.; Balligand, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
The modified Maquet technique (MMT) uses the same principle as the tibial tuberosity advancement (TTA) for stabilization of the cranial cruciate ligament-deficient stifle in the dog. In the MMT, the tibial tuberosity is advanced in a similar manner to that used in the TTA, however the means by which the tibial crest is stabilized differs. The plate and fork originally described by Montavon et al. are not used (7). The MMT was first described by Maquet for use on humans it leaves intact a distal bony attachment to the tibial shaft, and the tuberosity is either reinforced or not by a figure-of-eight wire. In this paper, we describe the MMT, and we report the results of our first 20 canine patients with cranial cruciate ligament rupture that were treated by the MMT. Mean clinical bone healing time was 6.8 weeks (range 4 to 12 weeks).The evidence provided by this Clinical Communication suggests that it is technically possible to achieve an advancement of the tibial tuberosity without the need for a plate. The MMT deserves consideration as a primary treatment option for cranial cruciate ligament rupture in dogs, and further evaluation in large clinical studies. Long-term follow-up and force plate analysis would be necessary to compare the MMT to both the TTA and the tibial plateau levelling osteotomy.
Keywords: Maquet; cranial cruciate rupture; tibial tuberosity advancement; dog